The multidisciplinary role of cultural management: a look for communication as management tool and key-activity - Tavares, S. A.; Ferreira, P. A.; Magro, N. (International Conference “Keep it Simple, Make it Fast! DIY cultures and global challenges” (KISMIF Conference 2021), 2021)
The purpose of this article is to explore the communication as tool and key-activity, within the scope of multidisciplinary character of cultural management and cultural equipment’s multimensionality. It's a hybrid study - conceptual and empirical - and exploratory, based on literature review and illustrated with descriptive analysis from data collected by 573 questionnaires regarding a specific event. Was followed a mixed methodology – qualitative and quantitative - and an interpretative paradigm. Were pulled out 3 conclusions: 1) The first one is the awareness need by the cultural management for an adoption of multidisciplinary posture, lined up by the multidimensional nature of cultural equipment’s and the organizational environment, in a purpose to match public expectations; 2) The second one is the need of comprehend the communication as tool and key-activity to engender culture value in both organizational environments: inside and outside; 3) The third, due questionnaire application, resides in the mass-media advantage over digitals, for public fund. This article: a) provides inputs for an interterritorial plan creation; b) contribute for the discussion about ideologic construction of professional category, instrands of thought building about its functions and concerns; c) increase communication importance as key-activity; d) highlight the power of media in cultural events; e) contributes to sign the need for a multidisciplinary training for cultural managers. The article value resides in reinforce the discussion for a new vision about the action ray of the cultural manager, supported in the connection between the equipment’s dimensions and the multidisciplinary posture.